4 A review of methods used for determining novel psychiatric research diagnoses in children and adolescents after acquired brain injury, and their limitations. Issue 8 (13th July 2017) - McCarron, Robyn
Abstract : Objective: To review the methods used for determining novel psychiatric research diagnoses in children and adolescents after acquired brain injury, and their limitations. Method: A literature search was conducted using EMBASE, Medline, PsycInfo, and CINAHL. 61 papers were identified, of which 18 met the inclusion criteria. The 18 papers were analysed in terms of their focus, participant characteristics, psychiatric disorders studied, evidence level, and the methods used for diagnosing novel psychiatric disorders. A grounded theory approach was used to classify any limitations identified in the papers. Results: The majority of studies focused on specific psychiatric disorders or symptoms. Most studies included participants with a broad range of ages and injury severity. Mood disorders, anxiety disorders and secondary ADHD were commonly studied. All studies used standardised assessment measures for determining psychiatric diagnoses. Most studies used structured clinical interviews, predominantly K-SADS. Limitations were identified relating to general study design, the participant. Conclusion: Studying novel psychiatric disorders after paediatric ABI is a highly important but challenging area. Further research is needed to assess the validity of current assessment methods, and to develop new tools for specific use in this population. Researchers in this area should be mindful of the multiple limitations faced, and address or acknowledge these where possible.